The coconut (Cocos nucifera L.) value chain and its productivity - Zambrano-Montesdeoca, Jasson (2021)
The present investigative work is developed in the Rio Chico parish, a rural sector of the Portoviejo canton, Republic of Ecuador, its main objective was to analyze the coconut value chain and its productivity in the Rio Chico parish. A study was carried out through descriptive, non-experimental and field methodologies, which approach the reality of the productive sector, on the other hand, the type of quantitative and qualitative research is evidenced, having analyzed the place of study, as well as tables and statistical representations, typical of this type of research. Likewise, representatives of the chosen ASOCOCOEBANITOS association, which produces Coconut Oil, a product analyzed in this work, intervened, so that the subject would indicate an in-depth study for a better development of this research. The results show that the Association does not have adequate marketing and distribution channels to be able to sell its product, they only do so for necessities and as it can be called safe sales, which affects both their own economy and that of the sector. , with regard to the transformation of the raw material to obtain products made from coconut oil, the process is very well managed by the inhabitants of the association, however, its chemical composition is not advised by professionals in the field, and production is not constant, the product is only made when there are fairs and when there are orders, which is not very common.